Aesthetic Education: A Perceptual-Cognitive Model - Ted Nannicelli (European Journal of Analytic Philosophy)
Here is a puzzle about aesthetic education. In a variety of contexts, we commit significant time, energy, and resources to aesthetic education. We teach (and in many cases publicly subsidize) university courses and degrees that have aesthetic education as their primary aim; we also invest public resources into museums, including enrichment programs that are also designed to afford aesthetic education. It would seem that if our commitment to aesthetic education is rational, then aesthetic appreciation is something that can be done better or worse. However, we also, in a variety of contexts (oddly enough, some of them being the same sorts of contexts that are designed to abet aesthetic education), act as if it is true that there is no disputing taste. We may try to persuade students to come around to particular judgments, but we do not penalize students for judging one way or another. The aim of this paper is to dissolve the apparent puzzle of aesthetic education by clarifying its aims and advancing a conception of it that deemphasizes the role of taste. I claim that, pace “the default view of aesthetic education” (as I shall call it), the primary purpose of aesthetic education is not to educate taste. It is, rather, to facilitate the development of certain perceptual-cognitive capacities so as to enhance aesthetic experience and improve aesthetic appreciation. Thus, I call the view of aesthetic education advanced here “a perceptual-cognitive model”.